2021
DOI: 10.3389/feduc.2021.678640
|View full text |Cite
|
Sign up to set email alerts
|

Improving Classroom Communication: The Effects of Virtual Social Training on Communication and Assertion Skills in Middle School Students

Abstract: This study examined the relationship between teacher identification of socially at-risk adolescents and baseline student social competency levels. Additionally, the feasibility and effects of an eight-session, virtual social training were analyzed. Upon completion of the virtual social training, the transfer effects from the targeted intervention into the general education classroom were determined. Study participants (N=90) were comprised of sixth, seventh and eighth-grade students from four public middle sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Supporting our hypotheses, Frontiers in Virtual Reality frontiersin.org current findings yield statistically significant improvements in emotion recognition, social inferencing, and social attribution accuracy. These findings are consistent with the training outcomes from our previous work (Didehbani et al, 2016;Johnson et al, 2021). Additionally, an added measure of social self-schemata demonstrated that CHARISMA-VST positively improved participants' sense of social self, indicating a potential mindset shift towards social resiliency.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Supporting our hypotheses, Frontiers in Virtual Reality frontiersin.org current findings yield statistically significant improvements in emotion recognition, social inferencing, and social attribution accuracy. These findings are consistent with the training outcomes from our previous work (Didehbani et al, 2016;Johnson et al, 2021). Additionally, an added measure of social self-schemata demonstrated that CHARISMA-VST positively improved participants' sense of social self, indicating a potential mindset shift towards social resiliency.…”
Section: Discussionsupporting
confidence: 88%
“…We hypothesized that children with social difficulties would demonstrate significant improvement following CHARISMA-VST in the areas of emotion recognition, social inferencing, and social attribution, consistent with our previous laboratorybased pediatric virtual reality social cognition studies (Didehbani et al, 2016;Johnson et al, 2021). Moreover, literature suggests a positive effect of social cognitive training on the formation of social schemata (Markus, 1997).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The study establishes LI as a significant facilitator of quality OLC. We also suggest that improved social skills can help instructors develop high quality LI (Johnson et al , 2021). Given the high and increasing importance of online learning, the findings of the study are highly significant for not only developing appropriate learning and development programs for corporates but also for formulating governmental policy.…”
Section: Discussionmentioning
confidence: 92%